Islamic Worldview Conceptions of Muhammadiyah Elementary School East Java Teacher on the Leadership of the Principal and Student Learning Outcomes - et. al., Sarwo Edy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to obtain an overview of the contribution or influence of the perception of Islamic worldview of the teachers on the leadership behavior of principals and the learning outcomes of students in Muhammadiyah Elementary School in East Java Indonesia through rational, emotional, organizational, family path, and family socio economic status (SES). Survey research design using proportional area random sampling technique based on the district / city of the school location. The data was taken through a questionnaire by the teacher, whose instruments were adopted and adjusted from the Leading Student Achievement (LSA) Elementary School Principal Survey Kenneth Leithwood. Data analysis techniques using Structural Equation Modeling (SEM), consisting of measurement models and structural models through the Analysis of Moment Structure (AMOS) program. Research hypothesis testing is done with path coefficient, by t test. The results of the Islamic worldview research that theoretically encompasses human behavior proved to have a direct effect on the leadership of the principal and teacher behavior in the classroom through rational and emotional paths. Indirect influence on learning outcomes is found through the leadership of the principal - rational path - organizational path. This study shows that in the religion-based schools Muhammadiyah, the Islamic worldview factor plays an important role in controlling the leadership behavior of principals and teacher learning in the classroom to achieve student learning outcomes. The results of the study also show that the only direct path of the influence of the principal's leadership on student learning outcomes is only through the rational path. And independently the family path affects student learning outcomes, but the socio economic status (SES) of the family has no influence.